(untitled) (Herald of Journalism, 2019)
This article considers special methods of public relations to achieve recognition and maintain status in the exhibition industry. The purpose of this article is to study the cumulative effect in the exhibition sphere. The article focuses on the study of the cumulative PR-effect on the example of the exhibition EXPO-2017, as well as analyses PR-technologies used in exhibition activities to create stability and significance of specially organized events. The idea of the article is to study the specifics of creating the image of the event and the cumulative PR effect. The scientific significance of the research is related to the fact that the work analyzes the specifics of promoting a large event, as well as PR technologies used to promote the exhibition industry, with the aim of increasing interest in exhibitions among the audience, attracting investors, and creating publicity in the exhibition field. The practical significance lies in the fact that this material can be used by marketers and public relations specialists in promoting the exhibition. The research methodology includes the method of theoretical research, historical, empirical and systematic methods of scientific research. We analyze the specific of creating a cumulative effect in the exhibition sphere, as a result of which it can be concluded that the requency of mentioning a particular event directly affects the memorability of it by the recipients. The practical significance of the work results is that the collected material and conclusions can be useful when reading courses in the specialty “Public Relations”, organizing and planning exhibitions, attracting participants and audience to them.